Meningkatkan Potensi Kerajinan Eceng Gondok di Desa Depok, Kapanewon Panjatan, Kabupaten Kulon Progo - Mayasari, Agatha (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Depok village is one of the villages that is located in Panjatan subdistrict, Kulon Progo district, this village has abundance of potency from water hyacinth handicraft. However, the farmers are still selling handcrafted bag from water hyacinth traditionally. This paper aims to educate and train the farmers of Depok Village on how to promote their water hyacinth handicraft products. This paper proposes to encourage every students to implement the knowledge obtained throughout their education for the purpose of granting knowledge and education to the people of Depok Village. With these KKN activities, the community becomes educated and could improve their economic level by utilizing the potential that exists in the village to be used as the source of income for the community in Depok Village. Due to the Covid-19 pandemic, this community service was conducted online, by collecting literature, collecting data online, developing discussions, and deciding on the results.